'He's not Rain Man': Representations of the sentimental savant in ABC's The Good Doctor. Issue 3 (1st October 2019) - Moore, Allison
Over recent years, representations of autism have increased in film, television and literature, including fiction and non-fiction, and yet the meanings ascribed to the condition, especially in popular culture, have become restricted rather than multiplied. All too often, autistic characters embody what Stuart Murray calls the 'sentimental savant', whose narrative function is to shine a light on the behaviour, attitudes and relationships of the non-autistic and expose their deficits in communication, interaction and empathy. In 2017, a new text was added to the growing body of representations of autism. The Good Doctor (2017–present) follows Dr Shaun Murphy who has autism and savant syndrome, as he navigates his first surgical residency. There is much that is positive about the show and it does challenge some stereotypes about autism. However, this article will argue that despite its progressive representations, the show does not veer too far away from the figure of the 'sentimental savant'. Shaun's autism is deployed not only to enrich the lives of his non-autistic colleagues but also to reinforce compulsory neurotypicality. Further, his extraordinary savant skills reflect and reinforce dominant metaphors of autism as alien or 'other worldly' and, in so doing, as not fully human.